Research Trend of Moral Hazard in Banking Industry - Firdaus Al Maidah; Kartika Ayu Kinanti; Yulian Ade Chandra (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2023)
Academic journals provide an important forum for the global academic community to interact and develop knowledge on the topic of moral hazard in the banking industry. Reviewing papers published between 2012 and 2023 can help academics acquire full knowledge of how this important topic has evolved over time and indicate new topics for additional discovery and investigation. The previous publications were assessed based on the annual number of articles published, author contributions, and research focus in their studies using a systematic analysis of a two-stage literature review. According to the review on moral hazard in the banking industry from 2012 to 2023, this research highlights the importance of conducting a comprehensive literature review due to the decline in published papers. It also examines the distribution of publications across various journals and explores a diverse range of topics within the field. The results highlight the significance of efficient risk management, regulatory supervision, and proper allocation of financial resources for maintaining a secure and sustainable financial system. Additional studies in these areas can enhance our knowledge and provide valuable insights to policymakers and professionals aiming to foster financial stability and promote responsible business practices.